Analisis Perbandingan Konsep Fikih Politik NU dan Muhammadiyah Perspektif Maqāṣid al-Syarī’ah - Wahyuding Wahyuding; Hamzah Hasan (Universitas Islam Negeri Alauddin Makassar, 2021)
The main discussion of this research is to provide an analysis of the comparative political fiqh between Nahdlatul Ulama and Muhammadiyah in the Maqasyid Sharia View. The discussion of Islamic political fiqh in Maqasyid Syariah, it turns out that in Islam there are three political concepts, namely formalistic, substantive and secularistic. Likewise with Nahdltul Ulama and Muhammadiyah, although there are often differences of opinion in politics, both of them have agreed that in politics it must be based on the amar maruf nahi munkar movement or as a da'wah movement. As the largest religious organization in Indonesia that has a social base on the grassroots, then NU and Muhammadiyah are given the right to be at the forefront in providing political education and also realizing substantial democracy in this country. Apart from the political ideals of the two Islamic organizations, we should also continue to integrate them with the true ideals of Islam, coupled with the political climate in Indonesia which often applies religion as a political trade, making us to continue to be careful in deciding the steps we take. will be traversed by Muslims in Indonesia